STRATEGIC IMPLICATIONS OF STOCK PERFORMANCE AND FINANCIAL STABILITY: EVIDENCE FROM INDONESIA & MALAYSIA - Rahma Febrianti; Wirda Mardyaningsih; Akhmad Ghozali; Bulan Nettiary Kelara (TECHNOBIZ : International Journal of Business, 2025)
This study aims to examine the influence of the Capital Adequacy Ratio (CAR), Return on Assets (ROA), and Gross Domestic Product (GDP) on the stock performance of publicly listed banks, proxied by the Price to Book Value (PBV), in Indonesia and Malaysia. Using a quantitative approach based on secondary data from annual financial reports and national macroeconomic indicators, multiple linear regression was employed to analyze both partial and simultaneous effects of the independent variables on stock performance. The findings reveal different relationships between the two countries. In Indonesia, CAR and GDP significantly affect PBV, while ROA shows no effect. In contrast, in Malaysia, all three variables—CAR, ROA, and GDP—significantly influence PBV. These results reflect differences in banking efficiency, financial stability, and investor sensitivity to fundamental indicators and economic conditions. This research enhances the understanding of how micro-level financial strength and macro-level economic performance jointly shape market perceptions of banking stock value. The results offer strategic insights for regulators, investors, and bank management to strengthen capital structure, sustain profitability, and align investment strategies with economic dynamics and market expectations across the ASEAN region.